Exploring alternative perspectives on millennial teachers' beliefs of and engagement with cultural and linguistic diversity: the use of reflective practice. Issue 3 (4th May 2022) - Hong, Huili; Knollman, Gregory; Doran, Patricia Rice
ABSTRACT: Reflective narrative is an essential practice that teachers and preservice teachers can use to: identify issues from their teaching; actively seek and reflect on solutions; and gain professional growth. Teachers' reflective practice regarding diversity has been widely researched in recent decades. However, as the new mainstream teaching force in schools with increasing culturally and linguistically diverse (CLD) children, millennial teachers (MTs) have been underrepresented in the body of research. In this multi-case study of millennial teachers (MTs), systematic and purposeful reflective practice has been employed as a pedagogical tool in preparing and supporting teachers of multilingual learners (MLs). The reflective narratives in the MTs' journals, interviews, and advocacy plans for CLD students were examined to explore the MTs' self-reflexive inquiries, discovery, and self-transformation. The MTs were found to hold an asset-based perspective of CLD students and see them as leaders, language brokers, and figures in their families and communities. Furthermore, the findings revealed MTs' improved engagement in diversity issues as advocates through expanded communication, understanding, connection, and collaboration with CLD students, families, ESOL teachers, mentors, and community members. This article concludes with the importance and affordances of using reflective practices in preparing teachers of and for CLD students.